2009
DOI: 10.1051/0004-6361/200810988
|View full text |Cite
|
Sign up to set email alerts
|

Binarity of transit host stars

Abstract: Context. Straight-forward derivation of planetary parameters can only be achieved in transiting planetary systems. However, planetary attributes such as radius and mass strongly depend on stellar host parameters. Discovering a transit host star to be multiple leads to a necessary revision of the derived stellar and planetary parameters. Aims. Based on our observations of 14 transiting exoplanet hosts, we derive parameters of the individual components of three transit host stars (WASP-2, TrES-2, and TrES-4) whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
183
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(205 citation statements)
references
References 34 publications
18
183
4
Order By: Relevance
“…They gave a projected separation between the TrES-2 host star and the companion candidate of (1.089 ± 0.008) . Our values for the projected separation of the dip relative to the center of the transit (see Table 5) is five orders of magnitude lower than the projected separation of the companion candidate Daemgen et al (2009) found. Thus, this companion candidate can not be the origin of the second dip in our light curves.…”
Section: Companioncontrasting
confidence: 71%
See 1 more Smart Citation
“…They gave a projected separation between the TrES-2 host star and the companion candidate of (1.089 ± 0.008) . Our values for the projected separation of the dip relative to the center of the transit (see Table 5) is five orders of magnitude lower than the projected separation of the companion candidate Daemgen et al (2009) found. Thus, this companion candidate can not be the origin of the second dip in our light curves.…”
Section: Companioncontrasting
confidence: 71%
“…First hint for the validity of this hypotheses gave Daemgen et al (2009). Using high-resolution "Lucky Imaging" with AstraLux at the 2.2 m Calar Alto telescope they found a companion candidate (physical association needs to be confirmed by second epoch observations) close to the TrES-2 host star.…”
Section: Companionmentioning
confidence: 99%
“…In most cases, the optimized value is close to the van Hamme value. The abnormally high value found for KOI 1.01 may be a result of it having a (visual) binary companion (Daemgen et al, 2009), thereby affecting the assigned (near solar) temperature. Table 5 allows assessment of the quality of the lightcurve fittings.…”
Section: Resultsmentioning
confidence: 95%
“…In order to derive approximate spectral types for the binary or multiple systems discovered in the AstraLux M dwarf survey and exclude background contaminants, each target was observed in SDSS i ′ -and z ′ -band and individual spectral types were derived from i ′ − z ′ colours and the integrated JHK spectral types, with estimated errors of ±1 spectral subtype (see Daemgen et al 2009;Bergfors et al 2010). Obtaining near-infrared spectral types allows us to Table 2.…”
Section: Comparison Of Near-infrared Spectral Types To Astralux Opticmentioning
confidence: 99%